Exploring 3D Cadastres in India: Evaluating the Potential for Land Planning, Development and Management in Delhi - Ghawana, T. (2020)
Based on the results, it is concluded that current practices related to 3D representation are immature and not adequate for capturing the future vertical growth of Delhi. This could lead to legal and physical boundary inconsistencies, irregularities, and dispute cases. However, adopting the international standard approaches, the agencies have the potential to enhance and support processes in the respective organizations. To realize this potential, internal and external factors related to policy, institutional setups, technical and financial arrangements need to be calibrated. It is recommended to initially focus on raising awareness for the widespread adoption of 3D representations in such organizations in Delhi.